2022
DOI: 10.1002/rcm.9401
|View full text |Cite
|
Sign up to set email alerts
|

Method optimization of the simultaneous detection of B12 congeners leading to the detection of a novel isomer of hydroxycobalamin in seawater

Abstract: Rationale More than half of surveyed microalgae and over 90% of harmful algae have an obligate requirement for vitamin B12, but methods for directly measuring dissolved B12 in seawater are scarce due to low concentrations and rapid light‐induced hydrolysis. Methods We present a method to detect and measure the four main congeners of vitamin B12 dissolved in seawater. The method includes solid‐phase extraction, separation by ultrahigh‐performance liquid chromatography and detection by triple‐quadrupole tandem m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Finally, a recent publication suggested that the dominant form of cobalamin in the North Sea was a putative OH-B 12 isoform that had similar fragmentation to OH-B 12 but eluted later (Möller et al 2022). We have not detected this putative isoform here or in any marine water column samples to date, despite our method's suitability for detecting this putative isoform's reported molecular ion in the proposed elution order (Supplemental Methods; Fig.…”
Section: Dominant Forms Of Cobalamin Expected In the Sunlit Oceanmentioning
confidence: 80%
See 3 more Smart Citations
“…Finally, a recent publication suggested that the dominant form of cobalamin in the North Sea was a putative OH-B 12 isoform that had similar fragmentation to OH-B 12 but eluted later (Möller et al 2022). We have not detected this putative isoform here or in any marine water column samples to date, despite our method's suitability for detecting this putative isoform's reported molecular ion in the proposed elution order (Supplemental Methods; Fig.…”
Section: Dominant Forms Of Cobalamin Expected In the Sunlit Oceanmentioning
confidence: 80%
“…In addition, calculating concentrations from response factors are difficult to replicate without exceptionally detailed experimental procedure reporting and data transparency. Quantification based on calibration curves performed in water instead of representative, pooled samples are common (Suffridge et al 2017;Möller et al 2022) and could significantly alter measurements due to intense matrix effects (Heal et al 2014;Boysen et al 2018). Third, Me-and Ado-B 12 standards are also subject to this rapid photodegradation and if great care is not taken to protect them from light during calibration curve construction, this degradation could lead to an overestimate of in situ concentrations.…”
Section: Dominant Forms Of Cobalamin Expected In the Sunlit Oceanmentioning
confidence: 99%
See 2 more Smart Citations
“…Figure 1 The flowchart of the measurement equipment According to the Beer-Lambert Law: A=εbc=log(I0/IT), when the path length is fixed, the quantity concentration of a substance is directly proportional to its absorbance. By measuring I0 and IT, and applying them to the standard curve, the quantity concentration of the substance can be calculated [4] . Based on the absorption curves of reaction products, suitable detection wavelengths are chosen, typically selecting wavelengths with strong absorption peaks.…”
Section: Measurement Principlementioning
confidence: 99%